2020
DOI: 10.31372/20200502.1088
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Attitudes Toward Lifelong Learning via New Technologies

Abstract: Introduction: Lifelong professional education is considered as a qualitative indicator in the health discipline, as it can improve health professionals’ knowledge and skills, as well as nursing care. Purpose: The purpose of this original research is to examine and record the attitudes and behavior of nurses working in state-run hospitals in the Municipality of Thessaloniki regarding lifelong education through new technologies. Identification of nurses’ motivations for lifelong distance education, recording of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Another challenge to rural nurses is that continuing education is not mandated as something employers need to provide to their employees. However, renewing and enriching knowledge is part of professional identity and an obligation for nurses (Lera et al, 2020;Rasmussen et al, 2021). Thus, nurses' attitudes and perceptions towards continuing education, as well as organizational Online Journal of Rural Nursing and Health Care, 23(1) https://doi.org/10.14574/ojrnhc.v23i1.723 support and supportive work environments are important in facilitating continuing education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another challenge to rural nurses is that continuing education is not mandated as something employers need to provide to their employees. However, renewing and enriching knowledge is part of professional identity and an obligation for nurses (Lera et al, 2020;Rasmussen et al, 2021). Thus, nurses' attitudes and perceptions towards continuing education, as well as organizational Online Journal of Rural Nursing and Health Care, 23(1) https://doi.org/10.14574/ojrnhc.v23i1.723 support and supportive work environments are important in facilitating continuing education.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, nurses' attitudes and perceptions towards continuing education, as well as organizational Online Journal of Rural Nursing and Health Care, 23(1) https://doi.org/10.14574/ojrnhc.v23i1.723 support and supportive work environments are important in facilitating continuing education. (Lera et al, 2020;Mlambo et al, 2021) Some of the strategies identified in this study to address barriers were collaboration and interprofessional education. Walmsley et al (2020) looked at practical approaches to normalize interprofessional collaboration in rural hospitals, highlighting the importance of positive workplace cultures and understanding of professions' roles.…”
Section: Discussionmentioning
confidence: 99%
“…Gad and Abou Ramadan 19 pointed out that elderly caregivers are unwilling to use new technologies, especially computer technologies, and prefer to avoid the opportunity to use computers. In addition, Lera et al 20 reported that older nurses tend to have a less positive attitude toward computer use and thereby a lower degree of acceptance of electronic information systems than younger people. 21,22 As most nurses at position level N have only recently graduated from schools and are relatively young, it naturally follows that they have a high acceptance of, and strong usage intention for, new technologies.…”
Section: Discussionmentioning
confidence: 99%
“…These nurses also understood that continuous learning was essential to the maintenance of their competency skills and the delivery of high-quality patient care (Price & Reichert, 2017). Furthermore, the results of the survey conducted by Lera et al (2020) showed that the majority of participants strongly agreed on the requirement of continuing education and stated two reasons for mandatory continuing education, which were to improve the quality of nursing care provided and to upgrade of the nursing profession. These findings are quite comparable to others that have been discovered in the past.…”
Section: Understandings Of Pd and Cnementioning
confidence: 99%